The Impact of Team Teaching on Student Attitudes and Classroom Performance in Introductory Philosophy Courses in advance. - Kotsko, A.
Despite the growing interest in collaborative teaching in higher education, there is a paucity of research on its use and effectiveness in philosophy curricula. The research that does exist focuses almost exclusively on interdisciplinary collaboration or student and faculty attitudes regarding the practice. This paper aims to address these gaps by describing a semester long, multi-section study designed to assess the impact of team teaching on student classroom performance and related variables in an Introduction to Philosophy course. The results of the study show that students overwhelmingly prefer team teaching to individual instruction and think that it positively impacts their learning and classroom experience. However, the results also show that there is no statistically significant relationship between delivery method and students? classroom performance. The paper concludes with a discussion of some limitations with the research design and the potential benefits and challenges of implementing team teaching within introductory philosophy courses.